Dvojinske in pluralizirane oblike v slovenskih narečjih - Jakop, Tjaša (Slavia Centralis, 2020)
Dual and Pluraliszed Forms in Slovene DialectsThe dual is a mandatory element of Contemporary Standard Slovene and also appears in the majority of Slovene dialects to varying degrees. As we shall see, some dialects are witnessing a gradual disappearance of the dual and its replacement by plural forms. In colloquial Slovene, which is by and large the spoken language of Ljubljana, the capital of Slovenia, the dual is still used for masculine nouns, while dual forms for feminine nouns have been replaced by the plural. The geographical extent of dual use is presented also statistically (statistics on dual use of noun and verb).
Keywords: dual; pluralisation; Slovene dialects; dialect morphology; dialectology